Fee-free Education Capitation Grants on Educational Facilities: A Case of Four Selected Government Secondary Schools In Ukerewe District, Tanzania (Tanzania Journal for Population studies and Development, 2022)
The article addresses the implementation of Tanzania’s fee-free secondary education Circular No. 5, which is complemented by capitation grants offered for improving students’ educational facilities in public schools. Specifically, it examines the process of allocating capitation grants to improve students’ learning facilities in selected government secondary schools in Ukerewe District, Tanzania. The article adopts the resource-based theory to explain the significance of improving learning facilities in secondary schools. A cross-sectional design was applied to conduct a survey in selected secondary schools. Data was collected through questionnaires served to a sample size of 96 respondents. Non-participant observation and focus group discussions were also conducted to collect in-depth information. Secondary data was collected through documentary reviews from various sources. Descriptive statistical analysis was applied to quantitative data to get frequencies and percentages in different scenarios that were determined through cross-tabulation. Qualitative data was analysed through content analysis to get detailed information about the study topic. The findings show that capitation grants provided for renovating students’ educational facilities were not sufficient to attain the required standards. Statistics indicate extreme deficits of classrooms. In addition, there was a scarcity of laboratories and libraries; one secondary school did even not have electricity. The article concludes that the process of improving students’ learning facilities has not been successful. Thus, the government should increase the amount of capitation grants for renovating and building students’ learning facilities to ensure that public schools are able to accommodate the rising number of students who are taking the advantage of the fee-free secondary school education.